Pengembangan Aplikasi Tabel Uap Portabel yang Mengintegrasikan IAPWS-IF97 dan CoolProp untuk Analisis Termodinamika - Agus Manggala; Muhammad Yerizam; Sahrul Effendy (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
The advancement of modern thermodynamic technology requires educational software capable of accurately calculating and visualizing the thermophysical properties of water and steam in accordance with the IAPWS-IF97 Industrial Formulation. This study presents the development of a standalone Python-based Steam Table application that integrates two thermodynamic property calculation backends, IAPWS-IF97 and CoolProp, into a single executable (.exe) package that operates without any additional installation. The application performs real-time calculations of thermodynamic properties, including enthalpy, entropy, pressure, and temperature, and provides interactive visualizations on h–s (Mollier) and T–s diagrams. The novelty of this research lies in integrating dual thermodynamic engines into an automated build-release system based on batch scripting, enabling efficient, reproducible compilation, version control, and distribution. Validation results show that the application operates stably in Windows 10–11 environments without external dependencies, producing results consistent with the IAPWS-IF97 reference tables, with a maximum deviation of less than ±0.05% across all tested state points. This tool is expected to serve as a lightweight, open-source, and adaptable platform for thermodynamic learning and research, particularly for studies involving the Rankine cycle, steam power plants (PLTU), and geothermal energy systems.